Kampung Batik Manding Siberkreasi sebagai Model Pelestarian Pendidikan Karakter - Azi Wansaka; Hernia Nur Hidayah; Hizma Arum Bakhittah (Universitas Negeri Malang, 2019)
Abstract. Batik is a series of mbat and tik. Mbat in Javanese is interpreted as ngembat or throw many times, whereas tik comes from the word titik. So, batik throwing dots repeatedly on the fabric. The points in batik are formed being a certain image will symbolize the character of the batik motif produced by every production house. This diverse batik motif is an illustration of how values are contained in the batik process. Perseverance, politeness, tenacity, and piety be the values contained in the batik process. However, nowadays it goes hand in hand over time the values contained in this batik process begin forgotten. This happens because of a lack of public understanding of the process batik. Kampung Batik Manding Siberkreasi is one form of preservation from community in Manding hamlet, Wonosari Gunung Kidul. Batik preservation this Wonosari community did this by establishing a Kampung Batik. In preservation is also taught in relation to the values contained within batik process, starting from the process of making motifs to coloring. These values are contained in this batik which can be a reference for characterDOI: http://dx.doi.org/10.17977/um033v2i22019p122